Response to antiretroviral therapy undergone by HIV/AIDS patients - Yasin, Nanang Munif; Maranty, Hesaji; Ningsih, Wahyu Roossi (Indonesian Journal of Pharmacy, 2011)
HIV/AIDS,  with  new  cases  thereof  coming  up  year  after  year,  is  a  fastgrowing  disease.  In  order  to  inhibit  HIV  replication,  ARV  is  administered  to HIV/AIDS  patients  throughout  his  life-time.  Continuous  monitoring  for  the detection of its desired result ought to be conducted. This study is aimed to find out  the  response  of  the  ARV  therapy  undergone  by  the  HIV/AIDS  patients hospitalized  in  a  teaching  hospital  in  Yogyakarta.  Descriptive  non-experimental design  was  used  for  the  study.  The  data  were  obtained  retrospectively  from medical records of 71 patients who met the inclusion and exclusion criteria. The data  were  analyzed  descriptively.The  research  findings  indicated  that  of  the first-line  ARV  therapy,  zidovudine+lamivudine+nevirapine  (AZT+3TC+NVP)  was mostly  used  (61.97%).  It  was  found  that  all  of  the  ARV  types  used  were  in accordance  with  the  National  Therapy  Antiretroviral Guidelines  (2007)  from Health  Ministry  Department,  Indonesia.  As  observed  further,  61  (92.80%),  40 (85.00%), and 20 (85.00%) patients had their CD4 increased; 66 (72.72%), 44 (75.00%), 24 (79.17%) had gained weight; and 71 (100%), 55 (100%), and 31 (96.77%) had survived the disease after 6, 12, and 24 months undergoing ARV therapy.  However,  the  increase  in  CD4 after  six-month  therapy  was  not  always attended  by  the  increase  in  weight.  To  conclude,  this  phenomenon  indicated good immune and clinical responses.Key words: HIV/AIDS, antiretroviral, therapy response, CD4count, hospital